An overview of agro-food industry wastewater treatment: a bibliometric analysis and literature review - Hesham Abdulla; Montserrat Zamorano; Miguel L. Rodríguez; Abeer El Shahawy; Sally Hosny; Jaime Martín-Pascual; Sahar El-Shatoury (Applied Water Science, 2022)
Abstract Agro-food (AF) industry provides great investment opportunities in its treated water and solid wastes, by conversion into value-added products. Our study accumulated extensive bibliometric data on this field from the Scopus database, between 1974 and 2021, and conducted a scientometric analysis using Science Mapping Analysis Software Tool (SciMAT) and VOSviewer for analyzing the retrieved data. The leading journals, highly used keywords in the published articles, authors and papers with the highest citations, and relevant regions were all identified in the scientometric analysis. Goal 6 of the Sustainable Development Goals (SDGs) pledge to “ensure the availability and sustainable access to water and sanitation for all.” To fulfill this demand, decentralized technologies are being developed. The scientometric analysis found significant flaws in previous studies on the adoption and use of decentralized treated AF wastewater, as well as its potential benefits for a sustainable future, particularly in the developing countries. Coagulation/electrocoagulation/ultrasonic processes, hybrid constructed wetlands and microbial inoculation are emerging efforts to achieve SDG6, particularly, in the emerging economy nations. Our scientometric findings can help academics collaborate on research, form joint ventures, and implement sophisticated technologies for treating AF wastewater and producing beneficial byproducts.